TEKNIK PENILAIAN DIRI BERBASIS GOOGLE FORM PADA MATA PELAJARAN PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN - Agustin, Anggi; Suryono, Hassan; Yuliandari, Erna (PKn Progresif, 2017)
The objectives of this research are to investigate: (1) the self assessment technique doesn?t optimum implemented. (2) to optimize the self assessment technique based on Google Form. (3) the impact of self assessment technique based on Google Form.This research used the qualitative descriptive research method. The data sources of research were informants, observations, and documentation. The samples of research were taken by using the purposive sampling technique. The data of research were collected through observation, in-depth interview, and documentation also validated by using the data and method trianggulations. They were then analyzed by using interactive model of analysis consisting of four main components, namely: data collection, data reduction, data display, and conclusion drawing.The result of research are as follows: (1) the self assessment which has been done by Pancasila and Civic Education teachers on SMK Negeri 2 Karanganyar only implemented once in a semester does not meet the assessment criteria. This was caused by several problems that self assessment require a lot of time while the time for learning is limited, many aspect of assessment that cause theacher?s performance is forced, requires a considerable cost, the lack of caring teachers to implement self assessment regularly because of limited time so self assessment is ignored by the teachers and teacher?s lack of understanding about self assessment. (2) Self assessment techniques based on Google Form can be delivered more optimum in ways of utilizing learning support facility as computer laboratory and wifi connection as maximum as possible. Implementation of self assessment based on Google Form is more efficient of time, cost, and teacher?s need not to forced. (3) The impact of self assessment based on Google Form were students can carry out self assessment as the discipline and also have a high interest towards self assessment based on Google Form. Impact on teachers that teachers can do a self assessment in a simple form, authentic, and more objective.